Chemical doping of unsubstituted perylene diimide to create radical anions with enhanced stability and tunable photothermal conversion efficiency - Che, Canyan; Tong, Shaohua; Jia, Yanhua; Yang, Jiaji; He, Xiandong; Han, Shaobo; Jiang, Qinglin; Ma, Yuguang (Frontiers in Chemistry, 2023)
N-doping of perylene diimides (PDIs) to create stable radical anions is significant for harvesting photothermal energy due to their intensive absorption in the near-infrared (NIR) region and non-fluorescence. In this work, a facile and straightforward method has been developed to control the doping of perylene diimide to create radical anions using organic polymer polyethyleneimine (PEI) as a dopant. It was demonstrated that PEI is an effective polymer-reducing agent for the n-doping of PDI toward the controllable generation of radical anions. In addition to the doping process, PEI could suppress the self-assembly aggregation and improve the stability of PDI radical anions. Tunable NIR photothermal conversion efficiency (maximum 47.9%) was also obtained from the radical-anion-rich PDI-PEI composites. This research provides a new strategy to tune the doping level of unsubstituted semiconductor molecules for varying yields of radical anions, suppressing aggregation, improving stability, and obtaining the highest radical anion-based performance.